Formulation and in vitro evaluation of pramipexole orally disintegrating tablets for pediatric restless leg syndrome - Turkmen, Omer; Pozharani, Leyla Beba; Amel, Moein (Marmara Univ, 2023)
In this study, orally disintegrating tablets (ODT) of pramipexole dihydrochloride monohydrate (PPX) was developed with direct compression method by using ready-to-use excipients Parteck (R) ODT, Pharmaburst (R) 500, Ludiflash (R), F-Melt (R), and Prosolv (R) Easytab SP for pediatric restless leg syndrome (RLS). The formulated ODTs were circular in shape with a total weight of around 100 mg, which was appropriate for pediatric use. In spite of very low content of the drug, content uniformity could be obtained successfully in accordance to the pharmacopoeial specification with a satisfactory mechanical strength in terms of hardness and friability. However, formulations based on Parteck (R) ODT and Ludiflash (R) could not achieve a disintegration time <30 s according to in vitro disintegration test, which was also supported by the simulated wetting test. The optimal ODTs based on Pharmaburst<(R)> 500, F-Melt (R) and Prosolv (R) Easytab SP were further evaluated for in vitro dissolution study. A very fast release of the drug was observed with these formulations that reached a peak value in 10 min., which was superior than that of the reference conventional tablet formulation of PPX. As a result, pediatric orally disintegrating tablets of PPX were successfully formulated with Pharmaburst (R) 500, F-Melt (R) and Prosolv (R) Easytab SP by using direct compression method with suitable characteristics, which can be further studied to use in pediatric RLS.
Keywords: Pramipexole; restless leg syndrome; pediatric; orally disintegrating tablets; direct compression; ready-to-use excipients